2018
DOI: 10.1097/01.ogx.0000530382.06730.2e
|View full text |Cite
|
Sign up to set email alerts
|

The End of Life Costs for Medicare Patients With Advanced Ovarian Cancer

Abstract: (Abstracted from Gynecol Oncol 2018;148:336–341) Most patients with advanced ovarian cancer will ultimately die of the disease. End-of-life care for ovarian cancer patients is often associated with a considerable expenditure of resources and costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
1
4
2
Order By: Relevance
“…We also found that being of black or Hispanic race/ethnicity was associated with higher amounts paid by Medicare during the final year, six months and 30 days of life. A recent publication assessing the cost of care at the end of life among ovarian cancer patients reported similar end of life costs to our analysis, supporting the accuracy of our estimates of costs [36]. Given the percentage of patients who elected to unenroll from hospice and undergo more invasive care, this finding of losing the reduction in the amount paid by Medicare is not surprising.…”
Section: Discussionsupporting
confidence: 84%
“…We also found that being of black or Hispanic race/ethnicity was associated with higher amounts paid by Medicare during the final year, six months and 30 days of life. A recent publication assessing the cost of care at the end of life among ovarian cancer patients reported similar end of life costs to our analysis, supporting the accuracy of our estimates of costs [36]. Given the percentage of patients who elected to unenroll from hospice and undergo more invasive care, this finding of losing the reduction in the amount paid by Medicare is not surprising.…”
Section: Discussionsupporting
confidence: 84%
“…The percentages for chemotherapy use in the last months of life in our cohort are lower than those reported in a large retrospective database study performed in the US including 5509 patients [6]. Several, mainly smaller, studies reported chemotherapy treatment in the last 14 days of life, with percentages varying between 5 and 13% [10][11][12][13][14][15], whereas it was 12% in the last month of life in our study.…”
Section: Discussioncontrasting
confidence: 89%
“…Almost a quarter of patients were admitted to hospital in the last month of life. This percentage is lower than those previously reported, which ranged from 43% to 57% [6,10]. Approximately 10% of patients visited the ER in the last month of life, which can be considered low.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…The American Society of Clinical Oncology (ASCO), the National Comprehensive Cancer Network (NCCN), as well as other national organizations have identified end of life care as a national priority and a core tenant of quality cancer care 16 17. As symptom management and avoidance of futile interventions are crucial at the end of life,18 19 it is important to evaluate whether trial participation encourages high intensity care prior to death. Our results differ from those presented in a prospective study of 358 patients with non-gynecologic cancers in which clinical trial participants experienced higher rates of aggressive end of life care in addition to chemotherapy administration 12.…”
Section: Discussionmentioning
confidence: 99%